Essential Norm of Products of Volterra-Type Operators and Composition Operators on Iterated Banach-Type Spaces - Rabab Alyusof; Shams Alyusof; Nacir Hmidouch (Axioms)
Let <semantics>H(D)</semantics> be the set of analytic functions on the open unit disk <semantics>D</semantics>. For <semantics>n∈N0:=N∪{0}</semantics>, define the iterated weighted-type Banach space <semantics>Vn:=<mfenced separators="" open="{" close="}">f∈H(D):supz∈D(1−|z|2)|f(n)(z)|<∞</mfenced>.</semantics> In this work, we study the boundedness and the essential norm of products of Volterra-type operators and composition operators on iterated weighted-type Banach spaces.